WHEN DONORS SET THE DIRECTION: LIMITS OF PROJECT-BASED HEALTH INTERVENTIONS IN LMICS – LESSONS FROM INDONESIA - Putri, Nuzulul Kusuma (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Health development in many low- and middle-income countries (LMICs) tends to be driven by donor-driven pilot projects frequently framed as innovative and scalable solutions. However, these programs typically disappear once external funding ends, resulting in the failure to achieve sustainability and long-term impact. This commentary explores the limitations of project-based development in LMICs, highlighting how shifts in the global aid architecture create complex pressures on recipient countries. Indonesia serves as a case study to illustrate how the proliferation of non-governmental organizations (NGOs) and competition for donor funding have led to fragmented implementation, donor-dependent strategies, and low levels of community ownership. Keywords: Donor-driven development, health program sovereignty, Indonesia, NGOs